The morphological and molecular characterization of Trichoderma spp. in cocoa agroforestry systems - Brito-Vega, Hortensia (Open Science Journal, 2020)
Species of the genus Trichoderma have been used as growth inhibitors and regulators of phytopathogens. The aim of this work was to study and molecularly characterize the species of the genus Trichoderma that can be found in the rhizosphere of cocoa agroforestry systems in the state of Tabasco, Mexico. Four composite samples were taken from each of three municipalities (Cardenas, Comacalco and Cunduacan). Thirty homogeneous sub-samples were taken (0-30 cm of depth) from each site (plantation) in a random zig-zag pattern across the middle part of the plantations, avoiding the edges. Thirteen strains of the Trichoderma genus were isolated and morphologically identified, while two species, T. harzianum and T. koningiopsi, were molecularly identified. Of the 13 strains, only five were amplified, and of these five, four corresponded to T. harzianum and one to T. koningiopsi.